Study of Contact Pressure Distribution in Bolted Encapsulated Proton Exchange Membrane Fuel Cell Membrane Electrode Assembly - Gui Ren; Yanfeng Xing; Juyong Cao; Ying Wang; Linfa Peng; Xuelong Miao (Energies, 2023)
The distribution of contact pressure on the Membrane Electrode Assembly (MEA) significantly affects the performance of a Proton Exchange Membrane Fuel Cell (PEMFC). This paper establishes a PEM fuel cell model to investigate the impact of bolt load and its distribution, sealing gasket hardness, and size on the magnitude and distribution of contact pressure on the MEA during assembly. Thermal–mechanical coupling is employed to simulate the thermal effects resulting from chemical reactions under operational conditions. The findings reveal that there is an extremum of pressure uniformity in the range of 5000 to 6250 N for bolt loads. When the average bolt load is lower than this extremum, altering the distribution of the load can effectively enhance the uniform distribution of contact pressure. Stiffer gaskets reduce the contact pressure on the MEA while increasing the pressure on the gasket itself, resulting in reduced deformation. A rational matching relationship among gaskets, Gas Diffusion Layers (GDLs), and seal grooves is proposed. During operational conditions, thermal effects decrease the sealing performance and also impact the magnitude and distribution of contact pressure on the MEA. These outcomes provide significant guidance for the assembly and performance evaluation of PEMFCs.